Muscular atrophy in diabetic neuropathy: a stereological magnetic resonance imaging study - Andersen, H.; Gadeberg, P. C.; Brock, B.; Jakobsen, J. (Diabetologia, 1997)
Diabetic patients with polyneuropathy develop motor dysfunction. To establish whether motor dysfunction is associated with muscular atrophy the ankle dorsal and plantar flexors of the non-dominant leg were evaluated with magnetic resonance imaging in 8 patients with symptomatic neuropathy, in 8 non-neuropathic patients and in 16 individually matched control subjects. In the neuropathic patients the muscle strength of the ankle dorsal and plantar flexors was reduced by 41% as compared to the non-neuropathic patients (p < 0.005). Volume of the ankle dorsal and plantar flexors was estimated with stereological techniques from consecutive cross-sectional images of the lower leg. The neuropathic patients had a 32% reduction in volume as compared with the non-neuropathic patients (p < 0.005). To determine the regional distribution of atrophy cross-sectional magnetic resonance images were performed at predetermined levels of the lower leg in relation to bone landmarks. In the neuropathic patients there was an insignificant increase of 3% of muscle area at the proximal lower leg level, whereas the atrophy was 43% (p < 0.002) at the mid lower leg level and 65% (p < 0.002) distally. Analysis of individual muscles confirmed that the atrophy predominated distally. We conclude that muscular atrophy underlies motor weakness at the ankle in diabetic patients with polyneuropathy and that the atrophy is most pronounced in distal muscles of the lower leg indicating that a length dependent neuropathic process explains the motor dysfunction.